Survival Strategies while Engaging in Deviant Behaviors: The Case of Amateur Waterboarding Torture. Issue 4 (2nd April 2020) - Balfe, Myles
ABSTRACT: This article explores personal management of health related risk in the context of amateur waterboarding torture-in effect, how people manage to 'survive' while trying out militarised psychomedical torture tactics for recreational reasons. In particular it examines why ordinary people torture themselves; their understandings of the seriousness of the risks that they are taking; and the strategies that they used to manage risk and ensure survival. 65 amateur waterboarding sessions are examined in total. Findings are contextualised in relation to Stephen Lyng's theory of edgework.